Dexmedetomidine alleviates CoCl-induced hypoxic cellular damage in INS-1 cells by regulating autophagy - Jin Ha Park; Ju Eun Oh; Namo Kim; Young-Lan Kwak (Korean Journal of Anesthesiology)
Background Ischemia-reperfusion (I/R) injury is inevitable during the perioperative period. The pancreas is susceptible to I/R injury. Autophagy, a self-digestion process, is upregulated during I/R injury and strongly induced by hypoxia. This study aims to determine whether dexmedetomidine can decrease pancreatic β-cell damage by regulating autophagy under hypoxia. Methods INS-1 rat insulinoma cells were cultured in dexmedetomidine before being exposed to cobalt chloride (CoCl2)-induced hypoxia. Cell viability and the expression of autophagy-related proteins (light chain 3B [LC3B]-II, p62, and ATGs) were assessed. The expression of apoptosis-related proteins (BCL-2 and P-BAD) were also evaluated. CoCl2-treated INS-1 cells were pretreated with the autophagosome formation inhibitor, 3-methyladenine (3-MA), to compare its effects with those of dexmedetomidine. Bafilomycin-A1 (Baf-A1) that inhibits autophagosome degradation was used to confirm the changes in autophagosome formation induced by dexmedetomidine. Results Dexmedetomidine attenuated the increased expression of autophagic proteins (LC3B-II, p62, and ATGs) and reversed the CoCl2-induced reduction in the proliferation of INS-1 cells after hypoxia. Dexmedetomidine also alleviated the decreased expression of the anti-apoptotic protein (BCL-2) and the increased expression of apoptotic protein (BAX). Dexmedetomidine reduces the activation of autophagy through inhibiting autophagosome formation, as confirmed by a decrease in LC3B-II/I ratio, a marker of autophagosome formation, in LC3B turnover assay combined with Baf-A1. Conclusions Dexmedetomidine alleviates the degree of cellular damage in INS-1 cells against CoCl2-induced hypoxia by regulating autophagosome formation. These results provide a basis for further studies to confirm these effects in clinical practice.